Effectiveness of binahong decoction water (Anredera cordifolia (ten) steenis) for perineal wound healing at home delivery aesya grabag Magelang, Indonesia - Wijayanti, Kartika; Esti, Rahayu Heni Setyowati (International Journal of Research in Medical Sciences, 2017)
Background: Puerperium period cause the changes for mother, both changes in physiological and psychological changes. One of the physiological changes that occur in women that their post-partum perineal laceration. The impact that occurs when wound healing is very unpleasant, like pain and fear to move, so it can cause many problems including uterus sub involution, lochea obstructed, and post-partum hemorrhage. Binahong leaves (Anredera cordifolia (Ten) Steenis) is one of the herbs that can be used as a wound healing with various preparations. This study aims to determine the effectiveness leaves binahong decoction water on perineum wound healing. Methods: The design of this study is a quasi-experimental design with two post-test with control group. Sample of this study is 44 post-partum mothers were divided into 2 groups, 22 people using binahong decoction water and 18 people using bethdine. Results: There is a significant difference perineal wound healing after given intervention binahong decoction water and bethadine. The percentage of respondents who experienced a perineal wound healing in binahong decoction water group better than bethadine group. Conclusions: Binahong decoction water very good for revitalizing the skin, giving extra stamina, blood circulation, resolve swelling and blood clots, restoring weak condition, and heal wounds. Binahong decoction water can be used as alternative technique to for perineum wound healing.